Influence of oxygen on performance of multi-principal element alloy as braze filler for Ni-base alloys. (3rd February 2023) - Schneiderman, Benjamin; Hansen, Alexander; Chuang, Andrew Chihpin; Yu, Zhenzhen
Abstract: In manufacturing of multi-principal element alloys (MPEAs), the casting process is often a primary point of oxygen introduction to the material system, which was demonstrated by the laboratory scale button arc-melting process. Oxygen introduction raises concerns for the mechanical performance of these alloys if employed as structural materials alone or in engineering applications, such as serving as filler materials to enable joining of similar or dissimilar alloy pairs that are conventionally considered difficult to join. In this work, oxide inclusions in an as-cast off-equiatomic MnFeCoNiCu MPEA and Ni-base alloy braze joints made with this MPEA were evaluated by synchrotron x-ray diffraction mapping and electron microscopy. MnO was found to be prevalent throughout the cast MPEA and was chemically reduced during brazing by trace Al from the base material, Ni-base Alloy 600. Incomplete reaction of the MnO with Al, and some alternative reaction with Cr, left a mixture of MnO, Al2 O3, and Cr2 O3 in the as-brazed joint, with the oxides concentrated near the braze centerline due to directional solidification. In the braze joints, the non-oxide constituent phases detected were an FCC matrix and particles of Cr23 C6, Cr7 C3, and TiN which are all native to Alloy 600. The evolution of oxides within the brazed joints at elevated service temperatures of 600–800 °C was also evaluated. While MnO and Al2 O3 were stable during high-temperature service, Cr2 O3 particles grew to several hundred microns, with dissolved oxygen in the MPEA providing a significant source for oxide growth. Comparing tensile performance of the as-brazed condition with post-service conditions showed that the evolution of oxide particles contributed to an increase in strength and decrease in ductility of the brazed joints. Evaluating particle morphologies among fracture surfaces of individual specimens demonstrated that large Cr2 O3 particles and continuous cluster networks of Al2 O3 were the features most detrimental to total elongation. Hence, unmitigated evolution of oxygen-containing species during brazing and service conditions is detrimental to the ductility of the brazed joints, which highlights the importance of oxygen control in initial manufacturing of MPEAs for engineering applications.